Microwave-induced temperature fields in cylindrical samples of graphite powder – Experimental and modeling studies. (August 2015) - Moon, Ethan M.; Yang, Chuqiao; Yakovlev, Vadim V.
Abstract: Microwave heating of graphite powder is the key process of a number of promising applications and emerging technologies ranging from kiln crucibles to synthesis of graphene. However, this process is typically studied in terms of structural parameters of the resulting products, whereas the prime electromagnetic and associated temperature characteristics remain insufficiently studied. In this paper, we investigate microwave heating of graphite powder in a batch (non-resonant) and waveguide (resonant) reactors using multiphysics (electromagnetic–thermal) modeling and experimentation. Temperature-dependent material parameters of graphite power are determined from measurements and appropriate physical models. Non-uniform temperature fields and their trend for relatively quick homogenization are shown to be conditioned by high values of the loss factor and thermal conductivity. These parameters are also found to be responsible for the effect of post-microwave heating. It is demonstrated that processing of graphite power in a resonant reactor may be convenient for controlling the heating rate and the level of temperature uniformity.